If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(x + 1) = 2x(x + 6) Reorder the terms: 3x(1 + x) = 2x(x + 6) (1 * 3x + x * 3x) = 2x(x + 6) (3x + 3x2) = 2x(x + 6) Reorder the terms: 3x + 3x2 = 2x(6 + x) 3x + 3x2 = (6 * 2x + x * 2x) 3x + 3x2 = (12x + 2x2) Solving 3x + 3x2 = 12x + 2x2 Solving for variable 'x'. Reorder the terms: 3x + -12x + 3x2 + -2x2 = 12x + 2x2 + -12x + -2x2 Combine like terms: 3x + -12x = -9x -9x + 3x2 + -2x2 = 12x + 2x2 + -12x + -2x2 Combine like terms: 3x2 + -2x2 = 1x2 -9x + 1x2 = 12x + 2x2 + -12x + -2x2 Reorder the terms: -9x + 1x2 = 12x + -12x + 2x2 + -2x2 Combine like terms: 12x + -12x = 0 -9x + 1x2 = 0 + 2x2 + -2x2 -9x + 1x2 = 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 -9x + 1x2 = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-9 + x) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-9 + x)' equal to zero and attempt to solve: Simplifying -9 + x = 0 Solving -9 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + x = 0 + 9 x = 0 + 9 Combine like terms: 0 + 9 = 9 x = 9 Simplifying x = 9Solution
x = {0, 9}
| e=x+4*666 | | 4-5(x-6)=3x-6 | | (x*204.73)+(y*160.92)=169.7575 | | =400x-5x^2-5 | | 8+4x+2x=80 | | y+12-6y=19 | | 3(4-y)/5=y | | x+5.3=8.17 | | 3+15=48 | | [n-35]/7=70 | | 6(x-6)-5(6-3x)=20(x-4)-8 | | (x*204.73)+(y*160.92)=178.41 | | x+(x-20)= | | 6x+6+7x=6 | | 5u^2+30=60 | | 29-5/3x=4 | | f(x)=3-4cos(x+1) | | 2x-3+5x=8 | | [k+27]*3=159 | | Z-5/4=3 | | 4x+2+6x=62 | | f=3-4cos(x+1) | | 5sinx-1=3sinx | | Tan^2(x)+2tan(x)+1=0 | | x=3-4cos(x+1) | | y+29=36 | | 7x+9+7x=37 | | 10=0.06(12.5)2+0.31(12.5)+4 | | 2x^3+9x+4=0 | | 36=4y+8 | | X^2-8x-18=2 | | (6x+22)=(x+37) |